2005
DOI: 10.1002/da.20080
|View full text |Cite
|
Sign up to set email alerts
|

Venlafaxine extended release versus conventional antidepressants in the remission of depressive disorders after previous antidepressant failure: ARGOS study

Abstract: Serotonin-norepinephrine reuptake inhibitors (SNRIs) may be used as an alternative treatment for depressed patients who do not tolerate or respond adequately to treatment with a conventional antidepressant. This randomized, open-label, multicenter study compared the effectiveness of the SNRI venlafaxine extended release (VXR) with that of conventional antidepressants (CA) in patients who were referred to an outpatient psychiatric specialty care setting for treatment after failure to tolerate or respond to at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 35 publications
2
32
0
Order By: Relevance
“…Unfortunately, the number of high-quality studies that investigated this issue is relatively small. The STAR*D [32] and the European ARGOS [33] trials have focused on this question, as have a limited number of RCTs.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, the number of high-quality studies that investigated this issue is relatively small. The STAR*D [32] and the European ARGOS [33] trials have focused on this question, as have a limited number of RCTs.…”
Section: Resultsmentioning
confidence: 99%
“…Using 3 randomized clinical trials (RCTs), including STAR*D, 12,14,15 Ruhe et al performed a systematic review. 16 Pooled results from 8 RCTs and 23 open-label studies showed a modest and "clinically equivocally advantageous" increased remission rate for venlafaxine over SSRIs (number needed to treat = 13 [95% confidence interval (CI) = 9.1-25.0]).…”
mentioning
confidence: 99%
“…62 Several other studies werea lso available for citalopram and escitalopram, 63 fluoxetine and sertraline, 64 and venlafaxine. [65][66][67][68][69] Because these studies did not necessarily report sufficient information to adjust both remission and response rates, an assumption was made that the results werec onsistent for both remission and response.…”
Section: Clinical Evidencementioning
confidence: 99%